Colorimetric determination of amaranth followed enrichment and separation using buoyant adsorbents - Shu Wu; Yuanyuan Yu; Cengceng Zhang; Fang Chen (Journal of Analytical Science and Technology, 2020)
Abstract A buoyant solid-phase extraction adsorbent was prepared by sodium alginate-coated hollow glass microspheres (HGMs) modified with 3-aminopropyltrimethoxysilane (3-APTS) for the separation and enrichment of anionic dye amaranth. After adsorbing amaranth, these low-density adsorbents can float on the surface of the solution, so the separation between adsorbents and substrates can be carried out by flotation. Quantitative determination of amaranth after separation and enrichment can be achieved by combining spectrophotometry. Under the optimum conditions, the linear range and detection limit for amaranth detection were 0.02 mg L−1–2.0 mg L−1 and 0.0021 mg L−1, respectively. The proposed method was applied to the determination of amaranth in different beverages, and the results were in good agreement with those by high-performance liquid chromatography (HPLC). The recoveries of amaranth in different beverages were between 97.93 and 105.91%. The floating adsorbent can be used as a conventional sample preparation method for the detection of low concentration analytes in complex samples.